Quantitative Modelling Methods for the Incorporation of Uncertainty into Construction Project Estimates - Adams, Russell John (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MEng (Civil Engineering))--University of Stellenbosch, 2006.